Strategi Komunikasi Bahasa Kasih dalam Inkulturasi Misi di Lembaga Pemasyarakatan Untuk Penguatan Iman Warga Binaan - Maramis, Fetrie JL; Sambo, Ferdie (Riviera Publishing, 2025)
This study examines the communication strategy of love language in the inculturation of missions in correctional institutions (prisons) to strengthen the faith of the inmates. The complex prison environment, full of psychological, social, and spiritual challenges, requires a holistic and relevant approach to mission. The concepts of love language – words of affirmation, quality time, gifts, acts of service, physical touch – introduced by Gary Chapman offer a unique framework for understanding and meeting the emotional and spiritual needs of individuals. The role of communication in the context of inculturation missions turns out that the language of love can function very effectively as a bridge that connects the teachings of faith with the reality of the lives of the inmates, facilitating the acceptance of religious messages in a more profound and personal way. This study uses a qualitative approach study with a case study method in one of the prisons in Indonesia. Data was collected through participatory observation, in the form of daily conversations for several years in great depth directly with the inmates, as well as theoretical analysis related to religious development programs. Therefore, the results of the study show that the application and approach through the communication strategy of love language can effectively increase openness, trust, and participation of the inmates in religious activities. This contributes to the internalization of spiritual values, positive behavior change, and ultimately, the continued strengthening of faith. The implications of this study highlight the importance of paying attention to and separating the theoretical and pragmatic that occur in the daily lives of inmates so that it will be an important input in living life as inmates who still hope to have a very meaningful meaning in life even in the midst of limited conditions.